Functional Outcome Predictors in Patients With Ischemic Stroke After Decompressive Craniectomy in A Tertiary Care Center in North Karnataka - Mahantshetti, Prakash S.; Gautam, Abhishek; kalyanshetti, Nikhita; Sharma, Ela (Journal of Neonatal Surgery, 2025)
Background Large hemispheric infarctions due to Middle Cerebral Artery (MCA), Anterior Cerebral Artery (ACA), or Internal Carotid Artery (ICA) occlusions often lead to severe neurological deficits and high mortality (41–79%) with conservative management. Risk factors include atrial fibrillation, hypertension, diabetes, and coronary artery disease. Decompressive craniectomy (DC) improves survival but yields variable functional outcomes. Although trials like HAMLET, DECIMAL, and DESTINY support early DC, further research is needed, especially in low-resource settings. Objectives 1.To identify and analyze the key predictors influencing functional outcomes in patients undergoing decompressive craniectomy for ischemic stroke. 2.To refine selection criteria for patients considered for decompressive craniectomy in the context of ischemic stroke, enhancing prognostic assessments and individualized treatment plans. Methods A combined retrospective-prospective study of 71 patients with unilateral supratentorial ischemic stroke who underwent DC (Jan 2019–Jun 2024). Data included demographics, clinical scores (mRS, NIHSS, GCS), imaging findings, etiology (TOAST classification), and postoperative outcomes at discharge and 3-month follow-ups. Results Mean patient age was 49.76 years, with 21.13% over 60. Gender did not affect outcomes, but dominant hemisphere infarcts were linked to worse deficits. Hypertension was the most common comorbidity. Surgery within 48 hours led to significantly better outcomes. Pre-op clinical and radiological assessments predicted prognosis. Dyslipidemia showed a possible protective effect, and infarct location influenced early recovery. Conclusion Early DC and individualized care improve outcomes in ischemic stroke. Older patients benefit similarly, supporting their inclusion in surgical protocols. Hypertension control, cardiac monitoring, and attention to infarct location are critical for optimizing recovery